GAMBARAN PENGETAHUAN IBU HAMIL TENTANG ANEMIA DEFISIENSI ZAT BESI BERDASARKAN KARAKTERISTIK DI PUSKESMAS LOSARI KABUPATEN BREBES - Dea Riskha Fitriliana; Intan Monik Pratami; Aliyah Aliyah (Midwifery Care Journal, 2022)
Anemia of pregnant women is a condition in which there is a shortage of red blood and a decrease in hemoglobin of less than 9.5 g/dl in the body of pregnant women (normal Hb 11 g/dl). Data from the Losari Health Center, which examined pregnancy found 423 people, and those who did HB (Haemoglobin) checks were 132 people. From the examination, the following data were obtained who had anemia there were 30 people (22.72%). This type of research is descriptive with an observational research design. The form of non-probability sampling, sampling method with total sampling is usually done in specific case studies and is very homogeneous in the characteristics of the population. The tstudy used total sampling where the total sample of the population was 30 first trimester pregnant women, who have anemia because of deficiency of iron. The results showed that the knowledge of pregnant women about iron deficiency anemia was mostly sufficient (60%). Based on the parity of the results obtained (73%), most of them were primiparous. Based on the diet, the results (63%) showed that most of the diets did not vary. Based on the socio-economic results obtained (83%) most of the results are less ( 1 million/month). Suggestion of this study is that pregnant women pay more attention to eating patterns with good nutrition, for health workers to increase counseling, especially pregnant women, for Puskesmas to improve quality services for pregnant women.